New taxa of Agapetes (Ericaceae) from Myanmar - Tong, Yi Hua; Xia, Nian He (Phytotaxa, 2014)
A new species and a new variety of the genus Agapetes from Kachin State, Myanmar are described and illustrated here. Agapetes putaoensis sp. nov. can be easily recognized by its very short peduncles and small cylindric-conical corollas divided more than a half, and Agapetes wardii var. heterotricha var. nov. differs from the typical variety in having longer pedicels and puberulous pedicels and calyxes sometimes with glandular setae. The distribution map of these two new taxa is also provided.